2009
DOI: 10.1097/ijg.0b013e31817d23e0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Indiana Bleb Appearance Grading Scale and Intraocular Pressure After Phacotrabeculectomy

Abstract: Two years postphacotrabeculectomy increased bleb height, as measured by the IBAGS, was associated with a decrease in IOP, with a 1 point increase in IBAGS height score resulting in a decrease of 2.16 mm Hg. We found no association between bleb extent, vascularity, or the presence or absence of conjunctival microcysts. As there were no cases of bleb leak in this study this characteristic could not be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
5
1
1
Order By: Relevance
“…Similar to the study of Sacu et al [2], we found that microcysts were associated with a low long-term IOP. Concerning corkscrew vessels (no significant correlation) and encapsulation (significantly less in patients with low long-term IOP), our findings were different from those of Sacu et al Compared to the findings of Smith et al [16], we could not find a correlation between bleb height and complete success or IOP.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Similar to the study of Sacu et al [2], we found that microcysts were associated with a low long-term IOP. Concerning corkscrew vessels (no significant correlation) and encapsulation (significantly less in patients with low long-term IOP), our findings were different from those of Sacu et al Compared to the findings of Smith et al [16], we could not find a correlation between bleb height and complete success or IOP.…”
Section: Discussioncontrasting
confidence: 57%
“…Sacu et al [2 ]showed that corkscrew vessels and microcysts can help to predict the IOP development. Smith et al [16] found a correlation between bleb height and IOP after phacotrabeculectomy. The purpose of this retrospective study was to evaluate the prognostic value of the early postoperative WBCS for the long-term outcome of trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Trabeculectomy is the standard surgical modality for treatment of glaucoma. Several clinical studies have demonstrated that the presence of filtration blebs are associated with intraocular pressure (IOP) levels after trabeculectomy . Filtration bleb failure is caused in part by wound healing responses elicited during the operation.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that the presence of filtration blebs are associated with intraocular pressure (IOP) levels after trabeculectomy. [1][2][3][4][5] Filtration bleb failure is caused in part by wound healing responses elicited during the operation. Numerous risk factors, such as neovascularization in the anterior ocular segments, active uveitis, history of cataracts and/or vitreous surgeries, and failure of previous filtration surgeries, are significantly associated with a poor outcome of trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…1), are likely to be important in the maturation of human trabeculectomy blebs 30 . Bleb morphology is a poor predictor of IOP reduction, although a higher bleb is more likely to result in a lower pressure 31 . Most surgeons prefer a modestly elevated, diffuse, relatively large and posterior bleb for reasons of safety.…”
Section: Introductionmentioning
confidence: 99%